The Potential Role of sPD-L1 as a Predictive Biomarker in EGFR-Positive Non-Small-Cell Lung Cancer - Vesna Ćeriman Krstić; Dragana Jovanović; Natalija Samardžić; Milija Gajić; Jelena Kotur Stevuljević; Aleksandra Klisic; Ivan Soldatović; Damir Radončić; Marina Roksandić Milenković; Biljana Šeha; Nikola Čolić; Katarina Lukić; et al. (Current Issues in Molecular Biology)
Background/Objectives: A significant breakthrough in non-small-cell lung cancer (NSCLC) treatment has occurred with the introduction of targeted therapies and immunotherapy. However, not all patients treated with these therapies would respond to treatment, and patients who respond to treatment would acquire resistance at some time point. This is why we need new biomarkers that can predict response to therapy. The aim of this study was to investigate whether soluble programmed cell death-ligand 1 (sPD-L1) could be a predictive biomarker in patients with epidermal growth factor receptor (EGFR)-positive NSCLC. Materials and Methods: Blood samples from 35 patients with EGFR-mutated (EGFRmut) adenocarcinoma who achieved disease control with EGFR tyrosine kinase inhibitor (EGFR TKI) therapy were collected for sPD-L1 analysis. We analyzed sPD-L1 concentrations in 30 healthy middle-aged subjects, as a control population, to determine the reference range. Adenocarcinoma patients were divided into two groups, i.e., a group with low sPD-L1 (≤182.5 ng/L) and a group with high sPD-L1 (>182.5 ng/L). Results: We found that progression-free survival (PFS) was 18 months, 95% CI (11.1–24.9), for patients with low sPD-L1 and 25 months, 95% CI (8.3–41.7), for patients with high sPD-L1. There was no statistically significant difference in PFS between the groups (p = 0.100). Overall survival (OS) was 34.4 months, 95% CI (26.6–42.2), for patients with low sPD-L1 and 84.1 months, 95% CI (50.6–117.6), for patients with high sPD-L1; there was also no statistically significant difference between the groups (p = 0.114). Conclusion: In our study, we found that patients with high sPD-L1 had numerically better PFS and OS, but this has no statistical significance. Further studies with a larger number of patients are needed to evaluate the role of sPD-L1 as a predictive biomarker in patients with EGFRmut NSCLC.